Steel drivin' man : John Henry, the untold story of an American legend - Nelson, Scott Reynolds (ACLS Humanities E-Book., 2006)
The ballad "John Henry" is the most recorded folk song in American history and John Henry--the mighty railroad man who could blast through rock faster than a steam drill--is a towering figure in our culture. But for over a century, no one knew who the original John Henry was--or even if there was a real John Henry. In Steel Drivin' Man, Scott Reynolds Nelson recounts the true story of the man behind the iconic American hero, telling the poignant tale of a young Virginia convict who died working on one of the most dangerous enterprises of the time, the first rail route through the App.